The Urgency Of National Land Law Reform In Responding To The Challenges Of Digitalization And Sustainable Investment - Antoni, Antoni (Jurnal sosial dan sains, 2025)
The development of digital technology and the push for sustainable investment require reform of national land law. Rigid legal systems, overlapping regulations, and limited spatial data are obstacles to realizing efficient, transparent, and accountable land governance. This article aims to examine the urgency of national land law reform in responding to the challenges of digitalization and the need for equitable investment. This study uses a juridical-normative method with a conceptual approach and critical analysis of applicable land regulations and policies. The results of the study indicate that land law reform must integrate the principles of good governance, digitalization of land services, and protection of community interests. The formation of regulations that are adaptive to technological developments and guarantee agrarian justice are the main prerequisites for providing legal certainty and supporting sustainable investment in the land sector.